EFEKTIFITAS PEMBERIAN VIRGIN COCONUT OIL (VCO) DAN LOTION TERHADAP KEJADIAN LUKA TEKAN (DECUBITUS) DI RUANG HIGH NURSING DEPENDENCY (HND) RUMAH SAKIT TELOGOREJO SEMARANG TAHUN 2023 - Antonius Yogi Pratama; Tri Endang Supriyanti (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
Background: In average, the patients who enter the High NursingDependency (HND) wards are the patients with total bed rest at risk of pressure wounds (Decubitus). Pressure wounds are one of the effects of hospitalization oncritical patients. In September 2022, there was one incident of pressure wounds out of a total of 1,030 patients. Pressure wounds can be prevented by maintainingthe integrity of the skin through the use of moisturizers by applying VirginCoconut Oil and lotions. Objective: to recognize the effectiveness of applying VCO and Lotion to the prevalence of pressure wounds Method: Quasi experimental quantitative with the design using two group pretest-posttest design. The sampling technique was purposive sampling technique. The samples were 42 respondents divided into two intervention groups; 21 people in Virgin Coconut Oil group and 21 people in Lotion group. The measurement tools were checklist sheet, pressure wound scale. Results: The result of the effectiveness test using the Mann Whitneyp value test is 0.638 (>0.05). The Wilxocon test in the Virgin Coconut Oil group value is 0.023 (<0.05), and the test in the lotion group is 0.034 (< 0.05). Then, it can be interpreted that there is an effect of applying Virgin Coconut Oil and Lotion on pressure wounds. Conclusion: There is an effect of applying VCO and lotion on pressure wounds. There is no significant difference between the uses of VCO and lotion. Recommendation: Researchers may apply Virgin Coconut Oil and Lotion toprevent pressure wounds (decubitus).